2020
DOI: 10.1002/jez.b.22947
|View full text |Cite
|
Sign up to set email alerts
|

Dark‐rearing uncovers novel gene expression patterns in an obligate cave‐dwelling fish

Abstract: Extreme environments often result in the evolution of dramatic adaptive features. The Mexican tetra, Astyanax mexicanus, includes 30 different populations of cavedwelling forms that live in perpetual darkness. As a consequence, many populations have evolved eye loss, reduced pigmentation, and amplification of nonvisual sensory systems. Closely-related surface-dwelling morphs demonstrate typical vision, pigmentation, and sensation. Transcriptomic assessments in this system have revealed important developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Nevertheless, we also found stronger expression of erythropoietic marker genes in the AGM and caudal hematopoietic tissue, which are involved in definitive hematopoiesis, implying that the second wave may also be expanded in cavefish. Further investigation will be required to determine whether erythrocytes are also increased in adults, although this possibility seems likely because adult cavefish have increased levels of hemoglobin transcripts ( Sears et al, 2020 ) and more erythrocytes in their head kidneys compared to surface fish ( Peuß et al, 2020 ). We conclude that cavefish have evolved a permanent enhancement in red blood cells as a potential adaptation for survival in hypoxic cave waters.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we also found stronger expression of erythropoietic marker genes in the AGM and caudal hematopoietic tissue, which are involved in definitive hematopoiesis, implying that the second wave may also be expanded in cavefish. Further investigation will be required to determine whether erythrocytes are also increased in adults, although this possibility seems likely because adult cavefish have increased levels of hemoglobin transcripts ( Sears et al, 2020 ) and more erythrocytes in their head kidneys compared to surface fish ( Peuß et al, 2020 ). We conclude that cavefish have evolved a permanent enhancement in red blood cells as a potential adaptation for survival in hypoxic cave waters.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of genes responsible for phenotypic adaptations in obligate cavefishes (A. mexicanus, S. typhlops, and S. anshuiensis) has revealed that different genetic mechanisms can lead to "many ways to build a cavefish, " as suggested in previous studies (Sears et al, 2020;Policarpo et al, 2021;Van der Weele and Jeffery, 2022). However, the identification of 73 shared genes between S. typhlops and other cavefishes suggests that molecular convergence also plays a significant role in cave adaptation, as previously observed in the Oca2 gene associated with the albinism phenotype in vertebrates (Protas et al, 2006); note that we were unable to retrieve Oca2 from S. typhlops.…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 73%
“…The investigation of genes responsible for phenotypic adaptations in obligate cavefishes (A. mexicanus, S. typhlops, and S. anshuiensis) has revealed that different genetic mechanisms can lead to "many ways to build a cavefish, " as suggested in previous studies (Sears et al, 2020;Policarpo et al, 2021;Van der Weele and Jeffery, 2022). However, the identification of 73 shared genes between S. typhlops and other cavefishes suggests that molecular convergence also plays a significant role in cave adaptation, as previously observed in the Oca2 gene associated with the albinism phenotype in vertebrates (Protas et al, 2006); note that we were unable to retrieve Oca2 from S. typhlops.…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 73%